An Improved GC-MS Method for Malondialdehyde (MDA) Detection: Avoiding the Effects of Nitrite in Foods - Wenjie Wang; Zhiwen Zhang; Xiaoying Liu; Xiaoji Cao; Lianzhu Wang; Yuting Ding; Xuxia Zhou (Foods, 2022)
Malondialdehyde (MDA) is one of the representative end products under lipid peroxidation, indicating the degree of lipid oxidation in foods. However, compounds in pickled products, especially the nitrite in salted lean pork can react with MDA under the acidic condition, leads to the loss of MDA and an underestimation on lipid oxidation through the conventional assay. In this study, the quantification for MDA in the sample containing sodium nitrite were found lacking accuracy by the thiobarbituric acid (TBA) assay and chromatography assay based on alkaline hydrolysis as the reaction between them were difficult to be completely inhibited. Among other trials, the improvement GC-MS analysis utilizing deuterium substituted MDA (MDA-d2) as an internal standard and applying perfluorophenylhydrazine (PFPH) as a derivative reagent can reduce the deviations from the presence of nitrite in the salted lean pork meat and the recovery is between 93.9% and 98.4% and coefficient of variation for the intermediate precision is between 1.1 and 3.5% using the method. The advanced gas chromatograph mass spectrometer (GC-MS) assay also has a very low detection limit (0.25 ng/mL) with both hydrolysis types.